Response of Trinexapac-ethyl-treated wheat to glyphosate drift - Orsolin da Silva, Diecson Ruy (2025)
The herbicide drift is problem in crops when it reaches non-target crops. The glyphosate drift after growth regulator application can influence in wheat response. This study assessed the effects of glyphosate drift after trinexapac-ethyl application on wheat. Two field experiments were conducted in winter season of 2018 and 2019. Cultivar TBIO Toruk and Sossego cultivars were used in 2018 and cultivar TBIO Audaz and Cultivar ORS Citrino in 2019. Wheat cultivars were treated with trinexapac-ethyl followed subdoses of glyphosate ranging from 0 to 72 g ae ha-1. The phytotoxicity from glyphosate was less than 10% to para Cultivar TBIO Toruk and Sossego. Glyphosate symptoms were slightly higher in cultivar TBIO Audaz cultivar treated with trinexapac-ethyl. The isolated effects of Trinexapac-ethyl and glyphosate reduced plant height, but the interaction of trinexapac-ethyl and glyphosate factors had a greater reduction on plant height in 2019. The interaction between trinexapac-ethyl and glyphosate promoted more damage  than they alone. Glyphosate reduced by up 11% cultivar TBIO Toruk yield but increase around 30% to cultivar Sossego yield. Cultivar TBIO Audaz was the most sensitive cultivar, with yield losses of up to 59% due to glyphosate drift. Overall, the effect of glyphosate on plant height was subdose dependent. Subsequent application of trinexapac-ethyl to plants exposed to the highest glyphosate subdoses resulted in decreased plant height and dry matter accumulation. Trinexapac-ethyl has no impact on wheat yield. The yield response was dependent of glyphosate subdose, cultivar and year.